If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -17 + 31 + 9x + -69 + -18x = -39 Reorder the terms: -17 + 31 + -69 + 8x + 9x + -18x = -39 Combine like terms: -17 + 31 = 14 14 + -69 + 8x + 9x + -18x = -39 Combine like terms: 14 + -69 = -55 -55 + 8x + 9x + -18x = -39 Combine like terms: 8x + 9x = 17x -55 + 17x + -18x = -39 Combine like terms: 17x + -18x = -1x -55 + -1x = -39 Solving -55 + -1x = -39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '55' to each side of the equation. -55 + 55 + -1x = -39 + 55 Combine like terms: -55 + 55 = 0 0 + -1x = -39 + 55 -1x = -39 + 55 Combine like terms: -39 + 55 = 16 -1x = 16 Divide each side by '-1'. x = -16 Simplifying x = -16
| 2x+200=12x-10 | | 12=1/5y-2 | | 10z-9z=-15 | | 2x^2+14x-20=0 | | 2+6x=-23+6 | | 2(x+y)=2x+y | | -3x-2x-4x=1 | | 8x-10=2x+3 | | 15/6x14/40x24/21 | | 2x-4x+8=6 | | 8+5=-3 | | p+5=-7 | | 4.4=10 | | 7-y=19 | | 4-1/4y=5 | | 4+x+x=20 | | 5x-3/8=x | | 4+x+x=30 | | Z=17-6 | | 7s=16 | | 6m+8n= | | 2z/9-8=5 | | -1+4=-3+18x | | h=h+1 | | 3r+6=40 | | 2(a-20)+2a=5a(a-3)-2 | | m^2-10m+34=0 | | 3(k-3)=k-3 | | 3x-6=6x+11 | | 12x-4y+1=0 | | 9+7x=21+x | | 0.25q+0.05n=3.00 |